A cross-sectional study of gender-based violence against men in the rural area of Haryana, India - Jagbir Singh Malik; Anuradha Nadda (Wolters Kluwer Medknow Publications, 2019)
Background: Research across the globe highlights rights violations and abuses experienced by women and seldom are channeled toward any atrocities being experienced by men. Objectives: To find the prevalence, characteristics, and sociodemographic correlates of gender-based violence against men. Materials and Methods: It was a community-based, cross-sectional study using multistage random sampling in which a total of 1000 married men in the age group of 21-49 years were interviewed using modified conflict tactics scale. Results: In the present study, 52.4% of men experienced gender-based violence. Out of 1000, males 51.5% experienced violence at the hands of their wives/intimate partner at least once in their lifetime and 10.5% in the last 12 months. The most common spousal violence was emotional (51.6%) followed by physical violence (6%). Only in one-tenth cases, physical assaults were severe. In almost half of the cases, husband initiated physical and emotional violence. Gender symmetry does not exist in India for physical violence. Less family income, education up to middle class, nuclear family setup, and perpetrator under the influence of alcohol were identified as risk factors. Earning spouse with education up to graduation is the risk factor for bidirectional physical violence. Conclusion: Besides women, men are also the victims of gender-based violence. This demands the future investigation and necessary intervention on gender-based violence against men in India.